"Being In On The Action" in Mobile Robotic Telepresence: Rethinking Presence in Hybrid Participation - Boudouraki, Andriana; Fischer, Joel E.; Reeves, Stuart; Rintel, Sean (HRI 2023, 2023)
Mobile Robotic Telepresence (MRP) systems afford remote communication with an embodied physicality and autonomous mobility, which is thought to be useful for creating a sense of presence in hybrid activities. In this paper, drawing on phenomenology, we interviewed seven long term users of MRP to understand the lived experience of participating in hybrid spaces through a telepresence robot. The users' accounts show how the capabilities of the robot impact interactions, and how telepresence differs from in-person presence. Whilst not feeling as if they were really there, users felt present when they were being able to participate in local action and be treated as present. They also report standing out and being subject to behaviour amounting to 'othering'. We argue that these experiences point to a need for future work on telepresence to focus on giving remote users the means to exercise autonomy in ways that enable them to participate — to be 'in on the action' — rather than in ways that simply simulate being in-person.